Variation in the biological half-life of methylmercury in humans: Methods, measurements and meaning - Rand, Matthew D.; Caito, Samuel W. (Biochimica et biophysica acta. General subjects, 2019)
Understanding methylmercury (MeHg) toxicity requires a complete understanding of its fundamental toxicokinetic and toxicodynamic characteristics in the human body. The biological half-life (t1/2) of MeHg is a kinetic property that directly influences the body burden of Hg that results from repeated exposures such as can occur with fish and seafood consumption. The t1/2 of MeHg in humans is approximately 50 days, equivalent to an elimination rate (kel) of 0.014 day−1. However, numerous studies report a wide range of half-life values (t1/2 < 30 to >120 days), demonstrating that significant variation in the biological process of MeHg elimination exists. This variation is a source of considerable uncertainty in deriving a meaningful reference dose for MeHg applicable to all individuals in a population. First, we summarize fundamentals of MeHg toxicokinetics, emphasizing the central role that biological half-life plays in MeHg dosimetry. We next present important considerations for how kinetic analyses are performed. We provide an example of how MeHg half-life variation directly influences the body burden and, in certain contexts, can result in MeHg levels exceeding the US EPA Reference Dose. We then survey existing studies that report MeHg half-life determinations in people. Recent advances in methods of determining MeHg kinetics in people have made individualized assessment of MeHg elimination rates more accurate and readily obtainable. Characterization of MeHg half-life, particularly in vulnerable individuals, such as pregnant women and children, will diminish the remaining toxicokinetic uncertainty surrounding MeHg exposures and will better inform the risk assessment process. •Biological half-life directly determines internal exposure and toxicity of methylmercury resulting from fish consumption.•Metabolism and elimination of methylmercury shows wide variation between individuals and within individuals over time.•Improved methodologies now make individualized determination of methylmercury metabolism and kinetics readily obtainable.•Advances in understanding methylmercury kinetics will lead to strategies to reduce toxicity risk.